Reactive Oxygen Species, Apoptosis, Antimicrobial Peptides and Human Inflammatory Diseases - Babatunji Emmanuel Oyinloye; Abiola Fatimah Adenowo; Abidemi Paul Kappo (MDPI AG, 2015)
Excessive free radical generation, especially reactive oxygen species (ROS) leading to oxidative stress in the biological system, has been implicated in the pathogenesis and pathological conditions associated with diverse human inflammatory diseases (HIDs). Although inflammation which is considered advantageous is a defensive mechanism in response to xenobiotics and foreign pathogen; as a result of cellular damage arising from oxidative stress, if uncontrolled, it may degenerate to chronic inflammation when the ROS levels exceed the antioxidant capacity. Therefore, in the normal resolution of inflammatory reactions, apoptosis is acknowledged to play a crucial role, while on the other hand, dysregulation in the induction of apoptosis by enhanced ROS production could also result in excessive apoptosis identified in the pathogenesis of HIDs. Apparently, a careful balance must be maintained in this complex environment. Antimicrobial peptides (AMPs) have been proposed in this review as an excellent candidate capable of playing prominent roles in maintaining this balance. Consequently, in novel drug design for the treatment and management of HIDs, AMPs are promising candidates owing to their size and multidimensional properties as well as their wide spectrum of activities and indications of reduced rate of resistance.